2010
DOI: 10.1007/s13181-010-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Frequency of Physostigmine Redosing for Antimuscarinic Toxicity

Abstract: We sought to determine how frequently antimuscarinic-poisoned patients receiving physostigmine receive multiple doses of physostigmine, the length of time between physostigmine doses, and what impact multiple doses of physostigmine have on the disposition and total length of hospital stay. We performed a retrospective chart review of patients given physostigmine for likely antimuscarinic toxicity. A total of 45 patients met inclusion criteria. We abstracted patient demographics, vital signs, physical exam find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Without the need for endotracheal intubation, our patient's length of hospital stay was drastically reduced. A study conducted in 2010 evaluating physostigmine use in anticholinergic delirium and hospital stay showed that 42% of patients were discharged directly from the emergency department, 31% were admitted to the general medical floors, and 27% were admitted to the intensive care unit with an average length of stay being 3.59 days [ 6 ]. A more recent retrospective study conducted in 2019 evaluated 141 patients in whom physostigmine was used demonstrated reduced intubation rates without increased incidence of dangerous adverse events including bradycardia and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Without the need for endotracheal intubation, our patient's length of hospital stay was drastically reduced. A study conducted in 2010 evaluating physostigmine use in anticholinergic delirium and hospital stay showed that 42% of patients were discharged directly from the emergency department, 31% were admitted to the general medical floors, and 27% were admitted to the intensive care unit with an average length of stay being 3.59 days [ 6 ]. A more recent retrospective study conducted in 2019 evaluated 141 patients in whom physostigmine was used demonstrated reduced intubation rates without increased incidence of dangerous adverse events including bradycardia and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Physostigmine is a short-acting acetylcholinesterase inhibitor, which increases synaptic concentrations of acetylcholine for competition with the toxic muscarinic antagonist for the acetylcholine receptor. It is a tertiary amine, allowing for crossing of the blood brain barrier for reversal of central antimuscarinic effects [1,11]. Its first documented use for reversing anticholinergic delirium was in 1864 by Kleinwachter, who treated patients that had mistakenly consumed atropine [1,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, practice patterns vary widely with regard to the dosing and rate of administration of physostigmine [1]. When dosed appropriately, however, most patients who receive physostigmine in the ED require only a single dose [11]. To avoid toxicity and prevent unnecessary redosing, recent recommendations suggest a single dose of 0.5 to 1 mg of physostigmine given intravenously with a minimum delay of 10-15 min before redosing [1].…”
Section: Discussionmentioning
confidence: 99%
“…In complete responders the rate of delirium recurrence requiring repeated doses of physostigmine ranges from 31 to 90% . The frequency and timing of relapse appears to be due to the shorter half‐life and duration of action of physostigmine compared with many anticholinergic agents.…”
Section: Anticholinergic Toxidrome: Clinical Features and Diagnosismentioning
confidence: 99%